Rynek pracy na pograniczu polsko-niemieckim - aspekty instytucjonalne - Adamczuk, Franciszek; Graczyk, Andrzej (Labor Market in the Polish-German Borderland - Institutional Aspects, 2006)
The article presents the regional labor market in the Polish-German borderland. The features of regional labor market and types of trans-border links are presented. It has been found that regional and local labor market problems are not solved in full co-operation between regional partners. Experiences of institutions shaping the market in question have been analyzed. Consequently the lack of direct and mutual solutions that could ease labor situation in analyzed area has been identified. The authors analyzed unemployment trends in Polish borderline voivodships and poviats. The opening of goods and services markets has not improved situation in borderline labor markets, in comparison to national trends. The unemployment rate in borderline poviats has not been decreased compared to unemployment rate in borderline voivodships.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1138, s. 103-113